Restructuring Coinage: A Linguistic Strategy for the Development of Anaang Language (Czech Journal of Multidisciplinary Innovations, 2022)
In this study, we embarked on restructuring coinage as a linguistic strategy for the development of Anaang language. The strategies and technicalities of coinages are modalities devised for the development of languages. We employed library sources, 122 words extracted from NERDC 2000 template, glossary of registers of different professions. Others were lexical materials and the orthographies of Anaang Language. The theoretical framework of instrumentalism propounded by Punya Sloka Ray and Valter Tauli, as cited by Mesthrie et al (2000) was modeled. After careful research on restructuring coinage, it was found out that this technique concerns reconstruction of words using morphonomic patterns of the target language created out of the source language. This technique is adequate, reliable, attractive and creative for language development. Linguists are advised to adopt this case study for the development of languages